THERAPEUTIC COMMUNICATION AGAINTS LABOR OF KALA I AND KALA II IN PRIMIGRAVIDA AT KLINIK PRATAMA NIAR IN 2018 - Surahman, Rayi Al Hay; Hutabarat, Julietta (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
ABSTRACT Anxiety in labor can be reduced by using non-pharmacological method related to the basic purpose of reducing anxiety and transfer of pain in labor that is by doing therapeutic communication to patient with the aim to keep the patient and fetus as far as possible remain free from depressive effect by way of gives a sense of comfort so as not to interfere with uterine contractions. Therefore, the authors are interested to examine the effect of therapeutic communication on the first and second stage of labor in the mother primigravida. Research type was Quasi Eksperimen, and Non-Equivalent Control Group, sample 20 respondents (primigravida mother). Data analysis with Independent T-Test. From 10 respondents of the experimental group and 10 non experimental groups, the duration of the active phase in the experimental group averaged 272.00 minutes (Sd.14.56), the mean second time was 22.50 minutes (Sd 6.34 ), The mean duration of labor was 299.00 minutes (Sd.19,40), whereas the first non-experimental group in the first stage was on average 316.00 minutes (Sd.15,95), the second stage was 32.00 minutes (Sd .7,52), the mean duration of labor was 348.00 minutes (Sd.19,60). Test T-Test value p (0,000) <α (0,05) at time of I,value p (0,007) <α (0,05) at second stage and value p (0,000) <α (0,05) length of labor. It was concluded that there was an effect of therapeutic communication with the time period I and Kala II of labor. Keywords : Therapeutic Communication, Kala I and Kala II Childbirth